2018
DOI: 10.1007/s11678-018-0451-7
|View full text |Cite
|
Sign up to set email alerts
|

Anterior shoulder dislocation and concomitant fracture of the greater tuberosity

Abstract: BackgroundRecurrence rates after primary traumatic shoulder dislocation are distinctly high. We hypothesized that concomitant isolated fractures of the greater tuberosity are associated with low rates of persistent instability but decreased range of motion.MethodsBetween 2007 and 2013, 66 consecutive shoulders in 64 patients were treated for primary shoulder dislocation combined with an isolated fracture of the greater tuberosity with either a nonsurgical (48 shoulders, 72.7%) or surgical (18 shoulders, 27.3%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…Two studies reported exclusively on these patients. 19,20 In the remaining 14 studies, 33.9% of patients had fracturedislocations. 9,17,18,21e23,25e28,33e35,37 Six studies reported brachial plexus injuries in 13 (5.8%) patients 18e20,22,23,33 and 9 of them had poor outcomes.…”
Section: Associated Injuries and Union Time (Table 2)mentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies reported exclusively on these patients. 19,20 In the remaining 14 studies, 33.9% of patients had fracturedislocations. 9,17,18,21e23,25e28,33e35,37 Six studies reported brachial plexus injuries in 13 (5.8%) patients 18e20,22,23,33 and 9 of them had poor outcomes.…”
Section: Associated Injuries and Union Time (Table 2)mentioning
confidence: 99%
“…(Table 1). 2 authors offered fixation in fractures displaced >1 cm 26,29 5 authors did not mention any displacement criteria 20,25,30,31,35 Remaining 15 authors accepted a 5 mm fracture displacement threshold to proceed for fixation, though one of them 19 operated upon fractures displaced >3 mm if patients were younger than 65 years. For arthroscopic fixation, 2 authors 23,24 excluded fragments larger than 2 cm, and 4 excluded fractures extending beyond the surgical neck.…”
Section: Associated Injuries and Union Time (Table 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Those dislocations associated with a greater tuberosity fracture have less chance of recurrence and greater loss of movements of the shoulder. 19 In a meta-analysis to determine the natural history of anterior shoulder instability treated nonoperatively, the overall recurrence was 21%, but it was as high as 80% in boys less than 20 years. 20 Multiple studies have shown that surgical treatment is beneficial for the treatment of first-time dislocation in young males.…”
Section: Discussionmentioning
confidence: 99%
“…In early cases and with large bony Bankart lesions, an open reduction and fixation with screw give good results. 19 If fixation of the fragment is not possible, then a reconstruction procedure like the Latarjet procedure can be done. In cases where there is more than 25 percentage of glenoid erosion, there is a high failure rate for soft-tissue procedures, and they are better managed with an osseous reconstruction of the glenoid.…”
Section: Discussionmentioning
confidence: 99%